2016
DOI: 10.21037/jtd.2016.05.59
|View full text |Cite
|
Sign up to set email alerts
|

Surgery and pleuro-pulmonary tuberculosis: a scientific literature review

Abstract: Tuberculosis (TB) is still a major public health concern, mostly affecting resource-constrained settings and marginalized populations. The fight against the disease is hindered by the growing emergence of drug-resistant forms whose management can be rather challenging. Surgery may play an important role to support diagnosis and treatment of the most complex cases and improve their therapeutic outcome. We conducted a non-systematic review of the literature based on relevant keywords through PubMed database. Pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 94 publications
(113 reference statements)
1
30
0
4
Order By: Relevance
“…Tuberculosis (TB) remains a leading cause of mortality worldwide especially in low and medium income states where its incidence is the highest (1) and drug-resistant TB has developed into an escalating problem with serious public health consequences (2,3).…”
mentioning
confidence: 99%
“…Tuberculosis (TB) remains a leading cause of mortality worldwide especially in low and medium income states where its incidence is the highest (1) and drug-resistant TB has developed into an escalating problem with serious public health consequences (2,3).…”
mentioning
confidence: 99%
“…The need for surgery is estimated to have increased from 5% to 15% over the last 20 years owing to the growing emergence of MDR-TB. 4 In this study, intrathoracic infections were the indication for more than half of the procedures (10 decortications, 6 open thoracostomies, and 2 aspergillomas). Patients with empyemas had a history of tuberculosis treatment plus several attempts at chest tube drainage that failed to remove the pus.…”
Section: Discussionmentioning
confidence: 72%
“…For underlying clinical predicative factors, according to the results in present study, pleural thickness and packaged pleural effusion might be risk predictive factors of PTM. These severe statuses sometimes need surgical operation [20,21]. Pleural thickness was reported to be the predictor for PT, Ruiz reported [22] that PT with pleural thickness were more common in men, elderly people, however, other studies showed that age, symptoms and pleural thickness were not related with PT [18], therefore, although existed controversial conclusions, combined with above results, pleural thickness might be closely related to the occurrence of PTM because the location of PTM is accompanied by local pleural thickness [23].…”
Section: Discussionmentioning
confidence: 99%